1987
DOI: 10.1126/science.2432658
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Main Immunogenic Region and Toxin-Binding Site of the Nicotinic Acetylcholine Receptor

Abstract: The alpha-chain of the nicotinic acetylcholine receptor carries the binding sites both for cholinergic ligands and for most experimentally induced or naturally occurring antibodies to the native receptor. By means of expression cloning in Escherichia coli, fusion proteins were derived from specific fragments of a complementary DNA encoding the mouse alpha-chain, allowing the mapping of the toxin-binding site to residues 160-216 and the main immunogenic region to residues 6-85. This approach permits the indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
0
14

Year Published

1988
1988
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(84 citation statements)
references
References 27 publications
3
67
0
14
Order By: Relevance
“…Torpedo AChR a-subunit cDNA clones have been expressed in fragments in bacteria [36,37], as full-length clones in yeast [38] and cell lines [39,40]. The proteins in bacteria have been used to map the aBgt-binding site [36,37] and epitopes recognized by T cells in experimental autoimmune MG (EAMG) and MG (Melmes, A. et al, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Torpedo AChR a-subunit cDNA clones have been expressed in fragments in bacteria [36,37], as full-length clones in yeast [38] and cell lines [39,40]. The proteins in bacteria have been used to map the aBgt-binding site [36,37] and epitopes recognized by T cells in experimental autoimmune MG (EAMG) and MG (Melmes, A. et al, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…This labelling, however, occurs exclusively on the reduced receptor since in the native receptor, Cysi92 and 193 are linked by a disulphide bridge (Kao & Karlin, 1986;Mosckovitz & Gershoni, 1988). Subsequent studies, based on the binding of snake a-toxins to a-subunit fragments, to synthetic peptides (Wilson et al, 1985;Radding et al, 1988;MulacJericevic & Atassi, 1986;Ralston et al 1987), deletion mutants (Barkas et al 1987), or a-subunit fragments expressed in Escherichia coli transformants (Gershoni, 1987), as site-directed mutagenesis experiments , confirmed that the region containing contributes to the interaction of cholinergic ligands and snake a-toxins with the a-subunit.…”
Section: Identification Of Amino Acids Composing the Binding Areas Fomentioning
confidence: 92%
“…Bacteria have also been used to express recombinant nAChR subunits, despite bacterial cells lacking the machinery for appropriate post-translational processing. Indeed, specific binding of nicotinic radioligands such as [ 125 I]-α-bungarotoxin has been reported with bacterial-expressed subunit proteins [55,73,74]. Yeast cells have also been used as an expression system for nAChRs and have been shown to produce subunit proteins with molecular weights similar to those of native nAChRs, suggesting that nAChR subunits expressed in yeast undergo glycosylation and signal-sequence cleavage [75][76][77].…”
Section: Expression Of Recombinant Nachrs In Vitro and In Bacteria Anmentioning
confidence: 99%